Environmental Education and Climate Awareness: Teachers’ Perspectives in Schools of Sunwal Municipality - Sapkota, Babin Sharma; Dhakal, Narayan Prasad (Devkota Journal of Interdisciplinary Studies, 2026)
Environmental education has become increasingly significant in a world where climate change is reshaping natural systems and threatening human well-being. Recognizing teachers as central actors in shaping students’ environmental awareness, this qualitative study examines how school teachers perceive, interpret, and implement environmental education and climate-related content in their classrooms in Sunwal Municipality. Drawing on semi-structured interviews with tenteachers from public and private schools in Sunwal Municipality, the study explores their understanding of environmental issues, their day-to-day teaching practices, and the realities they confront in attempting to integrate meaningful climate education. The findings reveal that although teachers acknowledge the growing urgency of global warming and view environmental education as a fundamental part of students’ learning, they often feel constrained by limited resources, insufficient professional training, and rigid curriculum structures. These constraints leave many teachers feeling underprepared and unsupported despite their personal commitment to environmental awareness. The study underscores the need for sustained teacher capacity-building, greater access to experiential learning tools, and stronger institutional and policy-level support to ensure that climate education becomes an integral and effective component of the school experience